Development of the Halal Industry in Indonesia: Opportunities and Challenges after the Covid-19 Pandemic - Christanti, Yana Dwi; Widodo, Nova Maulud; Daroji, Choirul (PT. Riset Press International, 2023)
The halal industry in Indonesia after Covid 19 has experienced growth, with Indonesia's population of 229.6 million in 2020, it has not been able to make Indonesia a supplier country for the needs of halal commodities in the world, there are many challenges that deserve joint attention to make Indonesia the center of the world's halal industry as targeted by the government in 2024 there will be two challenges in general, namely external challenges and domestic internal challenges, while opportunities for the halal industry in Indonesia are in the halal food sector, Islamic finance, halal tourism and Modest fashion. For this reason, this study aims to look at the Development of the Halal Industry in Indonesia regarding Opportunities and Challenges in the Post-Covid-19 Pandemic. This study uses a literature study, a descriptive approach, data and information collected from various literature from secondary data. Through this research, the authors hope to contribute to a portrait of the halal industry in post-pandemic Indonesia, so that they can see opportunities for development.